2012
DOI: 10.5102/rbpp.v2i1.1678
|View full text |Cite
|
Sign up to set email alerts
|

<b> Aquisições públicas sustentáveis: o princípio da sustentabilidade encarado para além da questão ambiental </b> - doi: 10.5102/rbpp.v2i1.1678

Abstract: Possui graduação em Direito pela UNIVALI (2009) e em Administração pela Universidade de Brasília (2003). Pós-graduado em nível de especialização em Filosofi a também pela Universidade de Brasília (2004) e em Direito Público pela UNISUL (2009). Ocupa o cargo de Auditor Interno do Poder Executivo do Estado de Santa Catarina. Atua na área de auditoira, fi scalização e consultoria em licitações, contratos administrativos e convênios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is because sometimes the laws establish optional criteria, or still, loopholes in other laws are sought in order not to enforce them. Freitas (2012) investigated whether the differentiated treatment given to micro and small enterprises is a skillful way to guarantee the social and economic sustainability of these enterprises. To this end, it carried out a bibliographic analysis in which it found that sustainability in public purchases goes beyond environmental issues, as it reaches social, ethical, legal, political and economic dimensions.…”
Section: Theoretical Referencementioning
confidence: 99%
See 3 more Smart Citations
“…This is because sometimes the laws establish optional criteria, or still, loopholes in other laws are sought in order not to enforce them. Freitas (2012) investigated whether the differentiated treatment given to micro and small enterprises is a skillful way to guarantee the social and economic sustainability of these enterprises. To this end, it carried out a bibliographic analysis in which it found that sustainability in public purchases goes beyond environmental issues, as it reaches social, ethical, legal, political and economic dimensions.…”
Section: Theoretical Referencementioning
confidence: 99%
“…To this end, it carried out a bibliographic analysis in which it found that sustainability in public purchases goes beyond environmental issues, as it reaches social, ethical, legal, political and economic dimensions. A limitation that Freitas (2012) found is that the legislation on the subject is recent, and therefore it not very widespread, when compared to the USA, and that there are few scientific works in this area. Masera (2008) researched how public administration stimulated the development of Micro and Small Enterprises and analyzed whether these stimuli are according to Complementary Law 123/2006 and Federal Decree nº 6.204/07.…”
Section: Theoretical Referencementioning
confidence: 99%
See 2 more Smart Citations